The levels and trends of contraceptive use before first birth in India (2015–16): a cross-sectional analysis - Singh, Pragya (BMC Public Health, 2020)
BACKGROUND: Indian women are more prone to first birth at a relatively younger age after marriage. Also, we do not have sufficient literature available that focuses on contraceptive use before first birth. The analysis of the present study was done using data from the fourth round of National Family Health Survey (2015–16), India. The objectives of the present study were to measure the levels and trends of contraceptive use before first birth among Indian ever married women, aged 15–34 years. METHODS: The study includes 279,896 ever married women aged 15–34 years at the time of the NFHS-4 survey. To identify the socio-demographic determinants governing the pioneering study behavior, multivariable techniques have been used in the analysis. The statistical significance of the relationship between socio-demographic factors and contraceptive use prior to first birth was tested using a chi-squared test for association. Hosmer Lemeshow statistics and Nagelkerke R square have been used to check how well the logistic regression model fits the data. Map of India showing different zonal classification is made using the ArcGIS software version 10.3. RESULT: The trends of contraceptive usage show a decline in use before first birth and the various socio-demographic factors affecting the use of contraceptive before first birth are religion, caste, education, wealth index, media exposure, age at marriage and the zonal classifications. CONCLUSION: The noticeable result in this study is the comparative decline in contraceptive use by women in India before first birth in NFHS-4 with respect to previous NFHS done in India. The likelihood of using contraception before first birth is significantly affected by factors like place of residence, religion, caste, current age of women, age at marriage, education level of women, wealth index, media exposure and zonal classification.